Powszechna Organizacja „Służba Polsce” a materialne formy rewanżu pamięci - Kałużna, Joanna (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
The article is mainly concerned with the Public Organization “Service for Poland” (“SP”). Membership of the “SP” is presented as an example of the reason for demanding financial compensation. The first part of the paper contains information about forming “SP” and its organization structure. Then different aspects of the collective memory about “SP” are brought up. Finally, the article describes attempts of demanding financial compensation because of the reason of being “SP’s” member.